1994
DOI: 10.1002/anie.199416181
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Access to Organocerium(IV) Complexes: Synthesis and Structure of Bis[1,3,6‐tris(trimethylsilyl)cyclooctatetraene]cerium(IV)

Abstract: Extremely soluble, briefly air‐stable, and thermally more robust than expected are CeIV complexes such as 1 containing the Me3Si‐substituted cycloocta‐tetraene dianion as ligands. The metal atom in these complexes is sterically well shielded by an organic shell. The way is now free to investigate the reactivity of this class of compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
41
0
2

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 23 publications
3
41
0
2
Order By: Relevance
“…[19] Examples of organometallic Ce IV complexes are also rare. The synthesis of [CeA C H T U N G T R E N N U N G (cot) 2 ] [28] (cot = cyclooctatetraenyl) and related complexes, [29][30][31] combining a highly oxidising metal cation with a reducing anionic ligand, has led to intensive study and debate into assignment of the metal oxidation state. [32][33][34][35][36][37] The first Ce IV cyclopentadienyl complex [38] was the tris(cyclopentadienyl)-supported Ce IV isopropoxide (D) reported by Marks et al, [39] closely followed by the crystallographically characterised tert-butoxide analogue reported by Evans et al [40] We have demonstrated the synthesis of [CeL 4 ] (L= OCMe 2 CH 2 (CNCHCHNiPr); E).…”
Section: ] (Nn' = [N-mentioning
confidence: 99%
“…[19] Examples of organometallic Ce IV complexes are also rare. The synthesis of [CeA C H T U N G T R E N N U N G (cot) 2 ] [28] (cot = cyclooctatetraenyl) and related complexes, [29][30][31] combining a highly oxidising metal cation with a reducing anionic ligand, has led to intensive study and debate into assignment of the metal oxidation state. [32][33][34][35][36][37] The first Ce IV cyclopentadienyl complex [38] was the tris(cyclopentadienyl)-supported Ce IV isopropoxide (D) reported by Marks et al, [39] closely followed by the crystallographically characterised tert-butoxide analogue reported by Evans et al [40] We have demonstrated the synthesis of [CeL 4 ] (L= OCMe 2 CH 2 (CNCHCHNiPr); E).…”
Section: ] (Nn' = [N-mentioning
confidence: 99%
“…One of the most sterically encumbered cot ligands currently available is the 1,3,6-tris(trimethylsilyl)-cyclooctatetraenyl dianion (cot'''). [14,15] The dipotassium salt of this ligand is accessible through a deprotonation/desilylation reaction of 1,3,6,6-tetrakis(trimethylsilyl)cyclooctatriene with potassium hydride in refluxing THF. [14] The deprotonation/desilylation of 1,3,6,6-tetrakis(trimethylsilyl)cyclooctatriene with two equivalents of KH as reported in the literature affords the THF adduct [K 2 (thf) 3 ](cot'''), which partially loses THF upon drying under vacuum and is thus difficult to isolate in a well-defined state.…”
mentioning
confidence: 99%
“…[14,15] The dipotassium salt of this ligand is accessible through a deprotonation/desilylation reaction of 1,3,6,6-tetrakis(trimethylsilyl)cyclooctatriene with potassium hydride in refluxing THF. [14] The deprotonation/desilylation of 1,3,6,6-tetrakis(trimethylsilyl)cyclooctatriene with two equivalents of KH as reported in the literature affords the THF adduct [K 2 (thf) 3 ](cot'''), which partially loses THF upon drying under vacuum and is thus difficult to isolate in a well-defined state. We found that the corresponding DME adduct [K 2 (dme) 2 ](cot''') (1, Scheme 2; off-white, needle-like crystals) is much better suited as a cot''' transfer reagent, as it is perfectly stable with respect to loss of coordinated solvent even under vacuum.…”
mentioning
confidence: 99%
“…Zu den größten bekannten cot-Liganden gehört das 1,3,6-Tris(trimethylsilyl)cyclooctatetraenyl-Dianion cot'''. [14,15] Das Dikaliumsalz dieses Liganden ist durch eine DeprotonierungDesilylierung von 1,3,6,6-Tetrakis(trimethylsilyl)cyclooctatrien mit Kaliumhydrid in siedendem THF erhältlich. [14] Die Deprotonierung-Desilylierung von 1,3,6,6-Tetrakis(trimethylsilyl)cyclooctatrien mit zwei ¾quivalenten KH gemäß der Literaturvorschrift liefert das THF-Addukt [K 2 (thf) 3 ](cot'''), das beim Trocknen im Vakuum partiell THF verliert und daher nur schwer in definierter Form isoliert werden kann.…”
unclassified
“…[14,15] Das Dikaliumsalz dieses Liganden ist durch eine DeprotonierungDesilylierung von 1,3,6,6-Tetrakis(trimethylsilyl)cyclooctatrien mit Kaliumhydrid in siedendem THF erhältlich. [14] Die Deprotonierung-Desilylierung von 1,3,6,6-Tetrakis(trimethylsilyl)cyclooctatrien mit zwei ¾quivalenten KH gemäß der Literaturvorschrift liefert das THF-Addukt [K 2 (thf) 3 ](cot'''), das beim Trocknen im Vakuum partiell THF verliert und daher nur schwer in definierter Form isoliert werden kann. Wir fanden, dass sich das entsprechende DME-Addukt [19] und hat sich seitdem als ausgezeichnetes Hilfsmittel zur Charakterisierung von zweiwertigen Organoytterbium-Komplexen erwiesen.…”
unclassified